Praktik Responsive Feeding dan Hubungannya dengan Stunted Children and Obese/Overweight Mothers (SCOM) di Kota Semarang: Praktik Responsive Feeding dan Hubungannya dengan Stunted Children and Obese/Overweight Mothers (SCOM) di Kota Semarang - Purwanti, Rachma; Margawati, Ani; Wijayanti, Hartanti Sandi; Rahadiyanti, Ayu; Kurniawati, Dewi Marfu'ah (Universitas Airlangga, 2023)
Background: A double burden of malnutrition can occur at individual, household, or community levels. Objectives: This study analyzed the relationship between responsive feeding practices and Stunted Children and Obese/Overweight Mothers (SCOM) as a type of double-burden malnutrition at the household level. Methods: An observational analytical study with a case-control design was conducted in Semarang City between May and October 2022. The subjects of this study were mother-toddler pairs (children < 3 years old) with SCOM and non-SCOM conditions in Semarang. Inclusion criteria were as follows: mothers and toddlers in good health (mothers do not have diseases that require special diets, and toddlers are in good health at the time of the study) and the mother did not smoke or drink alcohol. Ratio SCOM: non-SCOM groups was 1:2. Maternal nutritional status was measured using the Body Mass Index (BMI). Stunting classification (PB/U or TB/U) used the WHO Anthro software version 1.03. Data analysis was performed using chi-square, Pearson correlation, and multiple logistic regression. Results: Poor responsive feeding practices occurred in 95.8% of the SCOM families. There was a correlation between the parents' educational level and the practice of responsive feeding. There was a correlation between responsive feeding attitudes and practices and SCOM. After controlling for sociodemographic characteristics, responsive feeding practice predicted SCOM with an Odd Ratio (OR) of 0.012 (0.001–0.191). Responsive feeding practices were correlated with the prevalence of SCOM. Conclusions: Most families with SCOM practice responsive feeding in poor categories. Responsive feeding practices were a predictor of SCOM.